Evaluation of a High-Level Metamodel for Developing Smart Contracts on the Ethereum Virtual Machine - Velasco, Gislainy Crisostomo; Vieira, Marcos Alves; Carvalho, Sergio T. (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain), 2023)
Developers of smart contracts face challenges such as the immutability of contracts and asset storage, which make the activity complex and errorprone. To make contracts safer and more reliable, Model-Driven Engineering (MDE) offers an alternative approach with an emphasis on the High-Level Metamodel for Smart Contract (HLM-SC), which allows for the high-level declaration of elements within a contract. This paper evaluates the HLM-SC using the MQuaRE framework to verify its conceptual validity with 11 external evaluators. The results demonstrated the acceptance of the metamodel. Additionally, this paper presents a guide on how to use HLM-SC to facilitate its adoption by developers. Finally, it demonstrates the application of HLM-SC in a scenario related to the NFT industry.